Implementasi Pemenuhan Hak Asasi Manusia Dalam Penerapan Deportasi Orang Asing di Wilayah Kerja Kantor Imigrasi Kelas III Non TPI Pamekasan - Indar Rohma Nurbaya; M. Syaprin Zahidi (Faculty of Law, Universitas Bhayangkara Jakarta Raya, 2023)
This article was created to find out about the implementation of Immigration Administrative Actions by the Class III Pamekasan Immigration Office in the form of deportation in accordance with legal regulations and human rights principles. Deportation is an act of forcing foreigners to leave Indonesian territory. Even with coercive measures, the deportation procedure must be in accordance with regulations and must not violate human rights. The author uses a qualitative descriptive method in this study. The final results in this study indicate that the implementation of Immigration Administrative Actions (TAK) has been carried out without harming human values and still prioritizing rules, based on Law no. 6 of 2011 concerning Immigration and Law of the Republic of Indonesia no. 39 concerning Human Rights.